Optimasi Friction Stir Spot Welding Dengan Stabilizer Interlayer Pasta Zink Pada Material Dissimilar Aa5052-Ss400 - Nota Ali Sukarno Nota; Lingga Arti Saputra; Abdul Aziz (Infotekmesin, 2026)
Joining aluminum and steel materials using Friction Stir Spot Welding (FSSW) still faces challenges, particularly regarding interlayer stability and the limitations of joint mechanical properties. Previous studies generally focused on FSSW without an interlayer or used an interlayer without an adequate stabilization mechanism, so the joint quality has not been optimal. Therefore, this study aims to investigate the effect of using a zinc (Zn) paste interlayer stabilizer on the mechanical properties of dissimilar Al 5052–SS400 joints. The experimental method was carried out by comparing FSSW joints without an interlayer and with a Zn interlayer stabilizer. Evaluation was conducted through shear tensile testing and hardness measurements. The research results show that the Zn interlayer stabilizer is able to significantly improve joint performance, with a maximum hardness value of 119 HV and the highest shear tensile strength of 4.8 kN at a dwell time of 12 seconds. These findings fill a research gap related to the role of interlayer stabilization in enhancing the quality of FSSW joints of dissimilar materials.